ANALYSIS OF THE ROLE OF OFFICERS IN IMPORT MALARIA CONTROL IN PANDEAN PUSKESMAS DISTRICT TRENGGALEK - Rike Dwi Anggraini; R Azizah (The Indonesian Journal of Public Health, 2020)
ABSTRACKMalaria remains a health problem in the world. In Indonesia, malaria is one of the causes of the outbreak  in the province of East Java. Pandean is a public health center thatcounted for large numbers in cases of malaria in Trenggalek. Although Pandean public health center has conducted treatment of imported malaria, the cases are still high. The purpose of this research is to analyze the role of officers in the implementation of discovery and treatment program of imported malaria, including the availability of human resources, training, knowledge and understanding of the auth. This research is a descriptive observational research. Respondents in the study were 8 people, including Program Managers Of Malaria, 2 Microscopic and 5 JMD in Pandean public health center area. Data retrieval was implemented with interviews against the respondents and secondary data searches in  Pandean. The results showed they have the good availability of human resources, but there is no the head of JMD yet. Officer of the discovery and treatment of malaria have had a good knowledge, they have received training, and also have a good working understanding of auth, malaria program officer Role has been good, but they need to keep the improvements including recruitment of the head of JMD to avoid duplicate tasks so that the control of imported malaria can run optimally. Keywords: Malaria import control, The role of officers, Public Health Center